Nine Lives of Neoliberalism - Dieter Plehwe; Quinn Slobodian; Philip Mirowski (Verso, 2020)
Neoliberalism is dead. Again. Yet the philosophy of the free market and the strong state has an uncanny capacity to survive and even thrive in crisis. This volume breaks with the caricature of neoliberalism as a simple belief in market fundamentalism to show how neoliberal thinkers developed concepts and approaches in economic theory, welfare regimes and science philosophy, perceived institutions from the family to the university, disagreed over issues from intellectual property rights and human behaviour to social complexity and monetary order, and sought to win consent for their project through new honours, disciples, and networks.
Additional information: The publication of this book was funded by the Open Access Publishing Fund of the Leibniz Association.
Keywords: 320; behavioral economics; economic theory; entrepreneurship; homo economicus; intellectual property rights; liberalism; market fundamentalism; neoliberalism; ordoliberalism; political theory; philosophy of science; think tank networks